Dark inside - Roberts, Jeyn (Simon & Schuster Books for Young Readers, 2011)
After tremendous earthquakes destroy the Earth's major cities, an ancient evil emerges, turning ordinary people into hunters, killers, and insane monsters but a small group of teens comes together in a fight for survival and safety.